A REVIEW OF THE MESOZOIC OSTRACOD GENUS LOPHOCYTHERE AND ITS CLOSE ALLIES - Whatley R.C.; Ballent S. (My University, 2004)
The progonocytherid cytheracean ostracod genus Lophocythere and its immediate allies in the Jurassic are reviewed. All known species of 16 genera are considered. We consider that only eight of these genera (Acanthocythere, Afrocytheridea, Aulacocythere, Fuhrbergiella, Lophocythere, Neurocythere, Terquemula and Trichordis ) remain valid; the eight rejected genera are Crucicythere, Cuvillierella, Dhrumaella, Infacythere, Nophrecythere, Paralophocythere, Pokornya and Tropacythere.
Keywords: MESOZOIC; OSTRACODA; PROGONOCYTHERIDAE; NEUROCYTHERINAE; LOPHOCYTHERE; SYSTEMATIC REVIEW; Mesozoic; Мезозой